A Study on Utilization of Maternal Health Care Services in Rural Area of Aurangabad District, Maharashtra - Kuldeep J Dabade; Sheetal K Dabade; Hrishikesh A Khadilkar (Medsci Publications, 2013)
Introduction: Poor access and utilization of antenatal and other health services continue to contribute to high maternal mortality rate along with other socioeconomic factors. Improving utilization of maternal health care services is a global challenge for the health system in low and middle income countries. Material and Methods: It was a community based descriptive cross-sectional study which was undertaken from August 2010 to July 2011 in 4 villages of Paithan taluka, of Aurangabad district. Respondent women who had less than 1 year child and should be resident of particular area for previous 2 years or more at the time of interview were included in the study. Simple random sampling was used for selection of villages. Results: In present study only 40.8% respondent women had their first antenatal visit in 1st trimester. Majority of the women 90.3% had institutional delivery. Out of 8(3.9%) deliveries assisted by untrained person in 4(1.9%) deliveries umbilical cord cut with unsterile instrument and of these 4(1.9%) deliveries in 2(1.0%) untrained person applied cow dung to umbilical stump. Conclusions: Awareness regarding three or more antenatal visits and registration of pregnancy in first trimester should be emphasized through health education campaign. In present study though negligible percentage of hazardous practice of application cow dung to the umbilical stump was observed. It should be averted through health education and promotion of institutional deliveries.